Donor-Specific Cell-Free DNA as an Emerging Biomarker of Organ Rejection after Liver Transplantation. (July 2018) - Goh, Su Kah; Do, Hongdo; Muralidharan, Vijayaragavan; Jones, Robert; Dobrovic, Alexander; Christophi, Christopher
Abstract : Introduction: There is an increasing interest in the use of donor-specific cell-free DNA (dscfDNA) as a non-invasive biomarker of organ health after transplantation. We have developed a PCR-based approach that readily measures dscfDNA. Using this approach, we evaluated the utility of dscfDNA in two separate cohorts of recipients. Methods: Deletion/insertion polymorphisms (DIP) were used to distinguish donor-specific DNA and recipient-specific DNA. Post-transplant dscfDNA was measured using a simple and novel probe-free droplet digital PCR (ddPCR) methodology. In the longitudinal cohort, dscfDNA was serially measured at days 3, 7, 14, 28 and 42 in 20 recipients. In the cross-sectional cohort, dscfDNA was quantified in 16 recipients (>3 months post-transplant) undergoing liver biopsies.\ Results: DscfDNA levels were reflective of organ health after liver transplantation. In the recipients who underwent uncomplicated transplantation, dscfDNA markedly reduced at day 7 and remained at a low median level of 76.45 (IQR: 50.60-108.90) dscfDNA copies/mL from day 14 onwards. Furthermore, dscfDNA was consistently lower in recipients who did not have any evidence of rejection compared to those who developed biopsy-proven organ rejection (281.50 dscfDNA copies/mL vs 1, 661.00 dscfDNA copies/mL respectively, p<0.05). The area under the receiver operator characteristic curve of dscfDNA was higher compared to routine serum liver biochemistry (dscfDNA: 0.818, ALT: 0.745, GGT: 0.627, ALP: 0.436). Conclusion: In this study, we demonstrated a readily performed methodology to measure dscfDNA. We also highlighted the utility of dscfDNA as a promising non-invasive biomarker for the surveillance of organ health and the diagnosis of organ rejection after liver transplantation.